Creation of Business Incubators in University Through the Perspective of Business Law - Muslim, Shohib; Sekamdo, Muhammad Aga; Purnomo, D (IJBLE Scientific Publications Community Inc., 2024)
One of the most important ways to promote innovation and entrepreneurship in higher education is to incorporate business incubators. However, there are other legal considerations related to the development and administration of these incubators, including commercial law and educational legislation. The legal framework governing the creation of business incubators in higher education institutions is examined in this qualitative investigation. The study examines liability concerns, contractual agreements, intellectual property rights, and regulatory compliance through interviews and document analysis. The results shed light on the difficulties and possibilities present in academic business incubation programs, providing legislators, college administrators, attorneys, and other interested parties with useful information